System zabezpieczenia społecznego w polskiej polityce finansowej w warunkach UE - Antoniszyn, Emil (The Social Protection System as Part of Polish Financial Policy with Respect to EU Legal Regulations, 2007)
Pensions systems in the EU countries are not the same. The differences among these systems are associated with some specific elements, which reflect the most important theoretical aspects of pension protection systems construction. Among other general features the most important elements are: the time period of enacting important legal acts, which point to the last essential change in the system of a country in question, basic system features, which show the character of the system in a country, essentials rules of participation, defining the participation and accession to the system as well as exceptions from the duty accession. With regard to the basic system settlements, the most essential features are as follows: the minimum settled periods of membership in the system, necessary conditions to obtain a full pension, the condition of the pension age (standard, earlier and postponed) in every country. With regard to the rules of pension payment: the factors determining the receiving of the service, the formula of the service amount calculation, inclusion of non contribution periods in payments from the social service. The process of aging of the European society members and extension of the duration of older person's professional activity, force the politicians to look for new ways of social protections. In result of the last parliamentary elections in Poland, the society has been given a mandate to pro social turn in political parties programmes. A dozen years of economic reforms and spreading economic liberalism conceptions have led the majority of society to the fatigue and awoke concerns as to social policy outcomes, especially in respect to unemployment and improvements of health system. As one could observe, the reforms of the protection system in Poland have been performed radically and without social approval.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 43-53